Kajian Kebijakan Publik Menurut Tata Pemerintahan Yang Bersih Dan Berwibawa - ., Erika Fara Septia Ningrum; ., Moh. Adzib Zamroni; ., Urnika Ainurrohma; ., Uswatun Hasanah (CV. ITTC INDONESIA, 2022)
The National Development Program is to realize clean and authoritative governance. For this reason, appropriate policies are needed on institutional changes and management systems, the quality of human resources for apparatus, and an effective monitoring system. Policy studies are expected to generate and transform information about values, facts and actions. The purpose of this writing is to study public policy towards clean and authoritative governance. The writing method is carried out by conducting relevant literature studies both from books, journals and articles. So the state administration policy must be directed, to: 1) Close the abuse of authority in the form of KKN practices, 2) Growing the quality of state administration and, 3) Growing community empowerment in implementing development.